A wrinkled graphene and ionic liquid based electric generator for the sea energy harvesting. (3rd September 2019) - Zhen, Zhen; Li, Zechen; Zhao, Xuanliang; He, Yijia; Zhong, Yujia; Huang, Meirong; Wang, Min; Zhu, Hongwei
Abstract: Sea energy harvesting with carbon nanomaterials is an attractive renewable energy utilization strategy. Recently, studies with the focus on electric energy generation with various graphene-based materials combined with ionic fluids have been reported. However, reliable materials for the energy generation from the mechanical movements of seawater are still a challenge. In the present work, a wrinkled graphene based highly sensitive and stable electric generator has been developed and applied to multiple seawater movements with superior performances. The electric generation mechanism from the mechanical movements of seawater including droplet movement, boundary shift, and continuous flow is explored, and the corresponding electric generation performances are evaluated. The results suggest that the surface wrinkle nanostructure of graphene can enable energy harvesting from continuously flowing ionic liquid due to the drifting of adsorbed ions and ion accumulation in the wrinkles. Based on these results, a miniaturized sea energy harvesting system is fabricated and evaluated with simulated seawater flow and tidal waves. The as-fabricated generator exhibits high sensitivity and high voltage outputs, suggesting its great application potentials as a sea energy harvesting device.